Product Life Cycle and Promotion Strategies in Cellular Telecom Industry - Chandiran, P. (Indian Journal of Marketing, 2005)
Since the launch of the first cellular mobile service in August 1995, the Indian cellular industry has not looked back. Despite several hurdles in terms of policy and regulatory challenges, despite being on the verge of bankruptcy at the end of 1998, the industry has maintained its vigorous growth. During 2003, 17.7 million new subscribers were added, raising the total to 28.2 million. These services are now available in almost 1400 cities and towns and the customer base is growing by nearly two million every month.